Effect of hypothyroidism on the expression of nuclear receptors and their co-regulators in mammary gland during lactation in the rat - Campo Verde Arbocco, Fiorella (2015)
Thyroid hormones (TH) regulate mammary function. Hypothyroidism (HypoT) has deleterious effects on lactation, litter growth and survival. We analyzed the effect of chronic 6-propyl-2-thiouracil (PTU)-induced HypoT in the expression of nuclear receptors, co-regulators and oxytocin receptor (OTR) on lactation (L) days 2, 7 and 14. TH receptors (TRs) were increased on L7 at mRNA and protein levels, except TRα protein, that fell on L14. HypoT decreased TRα2 mRNA on L7 and TRα1 protein on L2, while TRβ1 protein increased on L14. HypoT increased estrogen receptor β (ERβ) mRNA on L7 but decreased its protein levels on L14. Progesterone receptor A (PRA) mRNA decreased from L2 to L14 while PRB increased, and at protein levels PRA levels showed a nadir on L7, while PRB peaked. HypoT decreased PRA mRNA and protein and increased PRB mRNA at L14. Nuclear receptor co-activator (NCOA) 1 and RXRα mRNA showed an opposite pattern to the TRs, while NCOA2 increased at L14; HypoT blocked the variations in NCOA1 and NCOA2. HypoT increased NCOR1 on L2 and decreased OTR at L2 and circulating estradiol and NCOR2 at L14.In controls the most notable changes occurred on L7, suggesting it is a key inflection point in mammary metabolism. The low levels of TRα1, NCOA1 and OTR, and increased NCOR1 produced by HypoT on L2 may hinder the mammary ability to achieve normal milk synthesis and ejection, leading to defective lactation. Later on, altered ER and PR expression may impair further mammary function.